2019
DOI: 10.1167/iovs.19-26993
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Ocular Features in Cases of Autosomal Recessive PROM1 Cone-Rod Dystrophy

Abstract: Purpose To define characteristic ocular features in a group of patients with autosomal recessive (AR) PROM1 cone-rod dystrophy (CRD). Methods Three males and one female from three unrelated families were first seen at the ages of 15 to 22 years and diagnosed with CRD. Clinical testing available for review included full-field electroretinogram (ERG) in three patients, as well as near-infrared autofluorescence (NIR-AF), spectral-domain optical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Prominin-1 is a membrane protein with five transmembrane domains that localizes at the open end of newly synthesized discs in ROS, thus opposite to the localization of Prph2 [51][52][53][54][55]. The vital role of Prominin-1 in the structural integrity of the photoreceptor OS is supported by the finding that mutations in Prominin-1 are connected to retinal diseases causing degeneration of the photoreceptors [54,[56][57][58][59]. Earlier studies on Prominin-1 demonstrated that it shows a binding preference for curved membranes, but does not induce the curvature itself [60,61].…”
Section: The Role Of Prph2 In Photoreceptor Outer Segment Morphogenesismentioning
confidence: 99%
“…Prominin-1 is a membrane protein with five transmembrane domains that localizes at the open end of newly synthesized discs in ROS, thus opposite to the localization of Prph2 [51][52][53][54][55]. The vital role of Prominin-1 in the structural integrity of the photoreceptor OS is supported by the finding that mutations in Prominin-1 are connected to retinal diseases causing degeneration of the photoreceptors [54,[56][57][58][59]. Earlier studies on Prominin-1 demonstrated that it shows a binding preference for curved membranes, but does not induce the curvature itself [60,61].…”
Section: The Role Of Prph2 In Photoreceptor Outer Segment Morphogenesismentioning
confidence: 99%
“…This group includes several proteins that play a role in eye morphogenesis in Drosophila and humans ( Jukam and Desplan, 2011 ; Mahato et al, 2018 ; Marrone et al, 2011a ; Ray et al, 2020 ). Moreover, these factors are not only associated with various ocular dystrophies but also involved in cancer development and regulation of stem cell maintenance and differentiation, cell growth, and metabolism ( Cehajic-Kapetanovic et al, 2019 ; Collison et al, 2019 ; Jamal et al, 2020 ; Lu et al, 2019 ; Priedigkeit et al, 2021 ; Wu et al, 2020 ). For example, in Drosophila, prominin (Prom), a homolog of human CD133, maintains mitochondrial function, regulates body size and weight, and influences animal longevity by controlling insulin and TOR signaling ( Ryu et al, 2019 ; Wang et al, 2019 ; Zheng et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is expressed in photoreceptors predominantly at the base of the outer segments in the protrusions of disk membranes ( Fig. 3 a) [35] , [36] , [37] . Prominin-1 interacts with cadherin related family member 1 (CDHR1) and actin to promote normal photoreceptor disk morphology [38] .…”
Section: Genes and Disease Mechanismsmentioning
confidence: 99%